Penerapan Prinsip Good Governance dalam Pengelolaan Lembaga Paud Berbasis Masyarakat: Studi Kasus Partisipasi Masyarakat Pada TK PKK 3 Gunungsari, Kabupaten Pasuruan - Dina Zuhrufia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the implementation of good governance principles, with a focus on the dimension of community participation, in the management of TK PKK 3 Gunungsari, a community-based Early Childhood Education (ECE) institution in Pasuruan Regency managed under the guidance of the village Dharma Wanita/Family Welfare Empowerment (PKK) organization. This research employs a qualitative approach using a single case study design. Primary data were collected through semi-structured interviews conducted on June 25, 2025, with the kindergarten principal as the key informant, supplemented by triangulation of perspectives from the supervisory board (PKK), teachers, and parents/guardians. The analysis refers to Cohen and Uphoffs (1980) four dimensions of participation: participation in ideas, labor, material contributions, and supervision. The findings indicate that community participation at TK PKK 3 Gunungsari is relatively well institutionalized. This is demonstrated through scheduled deliberation forums held every two months, the preparation of an activity calendar involving multiple stakeholders (the teaching staff, the village PKK Team, the village head, parents/guardians, and the district kindergarten supervisor), an installment-based contribution mechanism for parents/guardians experiencing financial difficulties, and financial reporting at the end of each semester and each year. The main supporting factor is the communitys sense of ownership of the institution as a village asset, while the inhibiting factors include the limited availability of working parents and a shift in patterns of community interaction toward digital platforms (WhatsApp groups), which has reduced the frequency of face-to-face meetings. These findings contribute to the discourse on public administration concerning the implementation of good governance at the micro-level of community-based public services. They also demonstrate that the success of participatory governance is strongly influenced by stable institutional leadership and support from village institutional structures. This study recommends strengthening the documentation of financial reporting through standardized written procedures, as well as conducting further research with a broader range of institutions and informants to obtain a more general understanding of participatory governance in community-based ECE institutions in Pasuruan Regency.